Underexploited tropical plants with promising economic value (National Academy of Science, 1975)
The apparent advantages of staple plants over minor tropical plants often result only from the disproportionate research attention they have heen given. Many indigenous species may possess equal merit, but were disregarded during the colonial era when consumer demands in European countries largely determined the cultivation priorites in tropical agriculture.